(untitled) (Ameghiniana, 2013)
The cuticle of Kurtziana brandmayri Frenguelli 1944 was studied with Scanning and Transmission Electron Microscopes (SEM and TEM). The specimens were found in the Nestares Formation (Jurassic), at Alicurá, a locality in Neuquén Province, Argentina. lt is now possible to suggest that Kurtziana brandmayri has its strongest affinities with the Cycadopsida. Also, stomata show several structures that suggest a strong xeromorphism of this plant.